2011
DOI: 10.1152/ajplung.00397.2010
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ signaling in lung epithelium regulates bleomycin-induced alveolar injury and fibroblast recruitment

Abstract: . TGF␤ signaling in lung epithelium regulates bleomycin-induced alveolar injury and fibroblast recruitment. Am J Physiol Lung Cell Mol Physiol 300: L887-L897, 2011. First published March 25, 2011; doi:10.1152/ajplung.00397.2010The response of alveolar epithelial cells (AECs) to lung injury plays a central role in the pathogenesis of pulmonary fibrosis, but the mechanisms by which AECs regulate fibrotic processes are not well defined. We aimed to elucidate how transforming growth factor-␤ (TGF␤) signaling in lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 57 publications
1
52
0
Order By: Relevance
“…As excessive amount of extracellular matrix was synthesized and deposited in the lung of Elovl6 À / À mice treated with BLM, and as TGF-b1 has an indispensable role in the activation of alveolar epithelial cells and myofibroblasts, the key effector cells in fibrinogenesis 39,40 , we sought evidence for whether Elovl6 deficiency may induce TGF-b1 expression in alveolar cells. As expected, we found that TGF-b1 mRNA levels were increased in the lung of Elovl6 À / À mice in comparison with WT mice, and TGF-b1 gene expression was upregulated by siRNA for Elovl6 in LA-4 cell.…”
Section: Blm Treatment Decreases Elovl6 Expression In the Lungmentioning
confidence: 99%
“…As excessive amount of extracellular matrix was synthesized and deposited in the lung of Elovl6 À / À mice treated with BLM, and as TGF-b1 has an indispensable role in the activation of alveolar epithelial cells and myofibroblasts, the key effector cells in fibrinogenesis 39,40 , we sought evidence for whether Elovl6 deficiency may induce TGF-b1 expression in alveolar cells. As expected, we found that TGF-b1 mRNA levels were increased in the lung of Elovl6 À / À mice in comparison with WT mice, and TGF-b1 gene expression was upregulated by siRNA for Elovl6 in LA-4 cell.…”
Section: Blm Treatment Decreases Elovl6 Expression In the Lungmentioning
confidence: 99%
“…To determine how increased TGF-β levels in the airways could contribute to fibrosis, HPS1 mutant mice were crossed with SPC.Cre/TGFBR2 f/f mice (19). Isolated type II AECs from HPS1/TGFBR2 ΔAEC mice showed minimal pSMAD2 signaling in response to TGF-β stimulation as compared with HPS1 controls, thus confirming effective reduction of TGF-β signaling (Supplemental Figure 5).…”
Section: And B) Following Bleomycin Treatment Hps2/mcp1mentioning
confidence: 87%
“…Other murine models utilized were bred onto the HPS backgrounds as summarized in Supplemental Table 1, including the following models from Jackson Laboratories: global CCR2-deficient (CCR2 -/-) mice (stock 004999), mice with loxP sites flanking exon 6 of the Tgfb1 gene (TGF-β1 f/f ; stock 010721), and mice with loxP sites flanking exons 2-3 of the Ccl2 gene (encoding MCP-1; MCP1 f/f ; stock 016849). LysM.Cre mice were as previously described (45), and mice with Cre recombinase under the control of the surfactant protein C promoter (SPC.Cre) were a gift from Brigid Hogan, Duke University (Durham, North Carolina, USA) (19,46). Mice were housed in the animal facility at Vanderbilt University, and studies were performed in both male and female mice.…”
Section: Methodsmentioning
confidence: 99%
“…TGF‐β1 mediates its effects via interactions among transmembrane receptors, including type I (TGFβRI), type II (TGFβRII) and type III (TGFβRIII). Upon binding to TGF‐β1, TGFβRII recruits and phosphorylates TGFβRI, which initiates signal transduction via Smad proteins 20. TGFβRII can transduce the TGF‐β1 signalling from cell membrane to the cytoplasm and then regulate a series of physiological or pathological processes including cell proliferation, differentiation 21, 22 and collagen production 23.…”
Section: Introductionmentioning
confidence: 99%